Low energy availability, menstrual dysfunction, and low bone mineral density in individuals with a disability: Implications for the para athlete population - Blauwet, C. A.; Brook, E. M.; Tenforde, A. S.; Broad, E.; Hu, C. H.; Abdu-Glass, E.; Matzkin, E. G. (Sports Medicine, 2017)
Low energy availability, functional hypothalamic amenorrhea, and low bone mineral density are three interrelated conditions described in athletic women. Although described as the female athlete triad (Triad), males experience similar health concerns. The literature suggests that individuals with a disability may experience altered physiology related to these three conditions when compared with the able-bodied population. The goal of this review is to describe the unique implications of low energy availability, low bone mineral density, and, in females, menstrual dysfunction in individuals with a disability and their potential impact on the para athlete population. A literature review was performed linking search terms related to the three conditions with six disability categories that are most represented in para sport. Few articles were found that directly pertained to athletes, therefore, the review additionally characterizes literature found in a non-athlete population. Review of the available literature in athletes suggests that both male and female athletes with spinal cord injury demonstrate risk factors for low energy availability. Bone mineral density may also show improvements for wheelchair athletes or athletes with hemiplegic cerebral palsy when compared with a disabled non-athlete population. However, the prevalence of the three conditions and implications on the health of para athletes is largely unknown and represents a key gap in the sports medicine literature. As participation in para sport continues to increase, further research is needed to understand the impact of these three interrelated health concerns for athletes with a disability, accompanied by educational initiatives targeting athletes, coaches, and health professionals.